Work-Life Balance and Its Role on Employee Performance in Public Sector: A Study in Public Universities in Nairobi City County, Kenya - Ngela, Roseline Mwikali; Kamaara, Mary (Journal Integration of Social Studies and Business Development, 2025)
This study examines the impact of work-life balance on employee performance within public universities in Nairobi County, Kenya. In recent years, public universities have faced scrutiny due to declining revenues, yet limited attention has been paid to employee implications, specifically their work-life balance. Beyond compensation and rewards, maintaining a suitable work-life balance is essential for employee productivity and focus. However, the ongoing crises in public universities raise concerns about the degree to which work-life balance is supported and how this affects employee productivity. The study aimed to evaluate the adoption of critical work-life balance elements—flexible work arrangements, organizational support, employee well-being, and social support—within these universities and to analyze their relationship with employee performance. The theoretical foundation for this research rests on the resource-based view and dynamic capabilities theories. Utilizing a descriptive research design, the study focused on administrative staff across two public universities in Nairobi County. A sample of 356 administrative employees was selected through a sampling formula, and data were collected using a structured questionnaire. Descriptive and inferential statistical methods were employed to analyze the data. The findings indicate that the universities have not effectively adopted flexible work arrangements, organizational support, employee well-being initiatives, and social support, which are essential components of work-life balance. Furthermore, these components were found to influence employee performance significantly. The study concludes that the inadequate implementation of work-life balance practices has adversely impacted employee performance in these institutions. Consequently, the study recommends that public universities enhance employee work-life balance by implementing flexible work options, improving employee well-being programs, and strengthening organizational and social support structures to bolster employee performance.